Essential notion of the health economic evaluation: Definition - Alexei Botchkarev (Atlantic Review of Economics, 2016)
Background: Economic evaluation (EE) is a dynamically advancing knowledge area of health economics. It has been conceived to provide evidence for allocating scarce resources to gain the best value for money. The problem of efficiency of investments becomes even more crucial with advances in modern medicine and public health which bring about both improved patient outcomes and higher costs. Despite the abundance of literature on the EE concepts, some key notions including the definition of the economic evaluation remain open for discussion. Academic literature offers a large number and growing variety of EE definitions. It testifies to the fact that existing definitions do not meet economists' requirements and they choose to create new definitions. Methods: The aim of this study is to explore existing definitions, identify knowledge gaps and formulate a comprehensive EE definition. Several methodologies were used to achieve the research objective: identification of related peer-reviewed papers using Google Scholar and EBSCO databases (e.g. MEDLINE Complete, CINAHL Complete, Health Business Elite, Health Policy Reference Center, Business Source Complete), critical literature review, critical thinking and inductive reasoning. Results: The study identified and examined 60 existing non-identical EE definitions, revealed their common focus points and grouped them into 8 clusters. Conclusions: Revealed common focus points were compared with the widely-accepted EE definition by Professor Michael Drummond and integrated in a comprehensive EE definition. A new, comprehensive definition of EE has been proposed.
Keywords: D61; I18; I10; I11; O3; 330; economic evaluation; health care; definition; evidence-informed policy; health technology assessment; health economics